A New Noncoding RNA Arranges Bacterial Chromosome Organization - Zhong Qian (American Society for Microbiology, 2015)
ABSTRACT Repeated extragenic palindromes (REPs) in the enterobacterial genomes are usually composed of individual palindromic units separated by linker sequences. A total of 355 annotated REPs are distributed along the Escherichia coli genome. RNA sequence (RNAseq) analysis showed that almost 80% of the REPs in E. coli are transcribed. The DNA sequence of REP325 showed that it is a cluster of six repeats, each with two palindromic units capable of forming cruciform structures in supercoiled DNA. Here, we report that components of the REP325 element and at least one of its RNA products play a role in bacterial nucleoid DNA condensation. These RNA not only are present in the purified nucleoid but bind to the bacterial nucleoid-associated HU protein as revealed by RNA IP followed by microarray analysis (RIP-Chip) assays. Deletion of REP325 resulted in a dramatic increase of the nucleoid size as observed using transmission electron microscopy (TEM), and expression of one of the REP325 RNAs, nucleoid-associated noncoding RNA 4 (naRNA4), from a plasmid restored the wild-type condensed structure. Independently, chromosome conformation capture (3C) analysis demonstrated physical connections among various REP elements around the chromosome. These connections are dependent in some way upon the presence of HU and the REP325 element; deletion of HU genes and/or the REP325 element removed the connections. Finally, naRNA4 together with HU condensed DNA in vitro by connecting REP325 or other DNA sequences that contain cruciform structures in a pairwise manner as observed by atomic force microscopy (AFM). On the basis of our results, we propose molecular models to explain connections of remote cruciform structures mediated by HU and naRNA4. IMPORTANCE Nucleoid organization in bacteria is being studied extensively, and several models have been proposed. However, the molecular nature of the structural organization is not well understood. Here we characterized the role of a novel nucleoid-associated noncoding RNA, naRNA4, in nucleoid structures both in vivo and in vitro. We propose models to explain how naRNA4 together with nucleoid-associated protein HU connects remote DNA elements for nucleoid condensation. We present the first evidence of a noncoding RNA together with a nucleoid-associated protein directly condensing nucleoid DNA.